A Case of Multiple Sclerosis—Like Relapsing Remitting Encephalomyelitis Following Allogeneic Hematopoietic Stem Cell Transplantation and a Review of the Published Literature - Das, Joyutpal; Gill, Atta; Lo, Christine; Chan-Lam, Natalie; Price, Siân; Wharton, Stephen B.; Jessop, Helen; Sharrack, Basil; Snowden, John A. (Frontiers in Immunology, 2020)
Complications involving the central nervous system (CNS) occur in 9–14% of patients following allogeneic hematopoietic stem cell transplantation (HSCT), including stroke-like episodes, demyelination, encephalitis, and nonspecific neurological symptoms. Here we report a case of multiple sclerosis (MS) like relapsing remitting encephalomyelitis following allogeneic HSCT, which did not respond to disease modifying therapies (DMTs) and “domino” autologous HSCT. A 53-year-old male was treated with allogeneic HSCT for lymphoid blast transformation of chronic myeloid leukemia. Ten months later he presented with confusion, slurred speech, left sided facial weakness and ataxia. A magnetic resonance imaging brain scan showed multiple enhancing tumefactive lesions. Neuromyelitis optica (NMO) and myelin oligodendrocyte glycoprotein (MOG) antibodies were negative. After extensive investigations for infections, autoimmune disorders and recurrence of malignancy, he underwent brain biopsy, which showed a macrophage rich lesion with severe myelin loss but axonal preservation indicating a demyelinating pathology. Although his symptoms improved with corticosteroids, he relapsed five months later. In the absence of any systemic features suggesting graft versus host disease (GvHD), his presentation was thought to be compatible with MS. The illness followed an aggressive course that did not respond to glatiramer acetate and natalizumab. He was therefore treated with “domino” autologous HSCT, which also failed to induce long-term remission. Despite further treatment with ocrelizumab, he died of progressive disease. An autopsy limited to the examination of brain revealed multifocal destructive leukoencephalopathy with severe myelin and axonal loss. Immunohistochemistry showed macrophage located in the perivascular area, with no T or B lymphocytes. The appearance was unusual and not typical for chronic MS plaques. Reported cases of CNS demyelination following allogeneic HSCT are very limited in the literature, especially in relation to histopathological examination. Although the clinical disease course of our patient following allogeneic HSCT resembled an “MS-like” relapsing remitting encephalomyelitis, the autopsy examination did not show any evidence of active inflammation. The impact of DMTs and HSCT on the histological appearance of “MS-like” CNS pathologies is unknown. Therefore, reporting this and similar cases will improve our awareness and understanding of underlying disease mechanisms.